Sum of Positive and Negative Responses as a Supplement of Balance in Qualitative Survey Data - Kowalewski, Grzegorz (Suma odpowiedzi pozytywnych i negatywnych jako uzupełnienie salda odpowiedzi w jakościowych badaniach koniunktury, 2011)
In most business tendency surveys, respondents usually have three options of choice, such as up, same and down. The balance is then calculated by subtracting the up percentage from the down percentage. When analysing balances only, the full information about the answers structure is rejected. To avoid this, it is appropriate to supplement the balances with additional rate: the percentage sum of positive and negative answers. In the paper the use of this indicator will be talked over and exemplified by GUS (Central Statistical Office) questionnaire data.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 164-176
Keywords: koniunktura gospodarcza; badanie jakościowe; business trends; qualitative research